Kekuatan Hukum Akta Otentik sebagai Bukti Sah Pelepasan Hak atas Tanah Ayahan Desa di Bali - Ida Ayu Nanda Parameswari; Ayu Putu Laksmi Danyathi (Acta Comitas : Jurnal Hukum Kenotariatan, 2025)
This study aims to determine the strength of authentic deeds of release of land rights over village land in Bali. The research method used is empirical legal research based on field research or field observations. The results of the study indicate that the function of authentic deeds of release of land rights before a notary is as a basis for the transfer of land rights from one party to another. Legal protection for land rights holders who have had their rights released is in the form of compensation that must be paid to the holders of the rights to the land that has been released. On the other hand, the party who obtains the rights to the land resulting from the release is protected by their right to own the land resulting from the release to ensure legal certainty regarding the acquisition of rights to the land resulting from the release. The legal strength of authentic deeds of release of rights is as a valid document in providing legal protection for land rights holders resulting from the release of rights in terms of providing compensation and clarity of land ownership status as regulated in the Agrarian Law.